The role of big data in transforming human resource analytics: A literature review - Jayalakshmi K.; M. Prabakaran (The Scientific Temper, 2024)
The growing integration of human resources (HR) analytics with big data analytics has transformed the way organizations manage their workforce, offering deeper insights into employee performance, recruitment strategies, talent retention, and overall organizational efficiency. This literature review explores the convergence of HR analytics and Big Data, highlighting key trends, methodologies, and challenges faced in this rapidly evolving field. It examines various HR analytics frameworks that leverage data-driven approaches to optimize human capital management, including predictive modeling, machine learning, and sentiment analysis. By reviewing a wide range of studies, this paper identifies the critical role of Big Data in enhancing decision-making processes, enabling more accurate predictions about employee behavior, and supporting strategic HR initiatives. Additionally, the review addresses ethical concerns related to data privacy, biases in algorithms, and the complexities of integrating Big Data tools into existing HR systems. The findings suggest that, while HR analytics has immense potential, the successful implementation of Big Data in HR requires a robust technological infrastructure, skilled professionals, and adherence to ethical standards. This review provides a comprehensive understanding of the current state of HR analytics and its future trajectory in the era of Big Data.